Towards the Adoption of ESAP-based Language Instruction for Undergraduate Students of Botany - M, Saritha; Nair, Bindu (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
English for Specific Academic Purposes (ESAP) envisages the tailoring of English instruction to the peculiarities and specific demands of students’ majoring discipline. Different disciplines place their own demands on English language resources. Therefore, the first step towards adopting ESAP based instructional strategies is to identify the peculiarities of a given discipline and its specific demands on the English language. This reflective article approaches English instruction for undergraduate students of Botany in the non-native context of Kerala, India from the ESAP perspective. The aim of this paper is to identify the peculiarities of Botanical discourses. Capitalizing the input provided by teachers of Botany and the analysis of Botany textbooks, we draw conclusions regarding the writing genres in Botanical discourses to be transacted in the ESAP based English sessions.